Complicaciones de la Colangiopancreatografía retrograda endoscópica (CPRE) - Coca Calle, Vanessa Nicole (2023)
ABSTRACT: The present research denominated Endoscopic retrograde cholangiopancreatography (ERCP), is a study that combines esophagogastroduodenal endoscopy with radiographs that starts as a diagnostic procedure. However, at present with the development of better techniques, it is used as a purely therapeutic study, being managed worldwide for various pathologies of the biliary and pancreatic tract that requires great technical skill by the specialist, and although the study is particularly useful, the procedure leads to multiple complications. The meet the objective of the present research, post endoscopic retrograde cholangiopancreatography (ERCP) complications in patients undergoing this procedure were analyzed, through a literature review collected from 2019 to 2023. The present research work was based on a descriptive, documentary, cross-sectional-retrospective study with a qualitative approach; using sixty-one bibliographic references obtained from different databases of great scientific relevance published in the last five years, in Spanish and English that met the inclusion criteria. According to the information analyzed based on meta-analysis studies, clinical practice guidelines, systematic reviews and observational studies, there was consensus that ERCP involves several complications, such as acute pancreatitis, hemorrhage, infections, and related perforations, therefore, health personnel must be trained to detect them. It is concluded that ERCP is considered a therapeutic procedure for various biliary tract pathologies, demonstrating great effectiveness as it was less invasive than other techniques. Nonetheless, it presented a high probability of multiple adverse events after its performance, which led health personnel to pay special attention to patients undergoing the study.